A review of research on the impact of professional learning communities on teaching practice and student learning - Vescio, Vicki; Ross, Dorene; Adams, Alyson (Teaching and Teacher Education, 2008)
After an overview of the characteristics of professional learning communities (PLCs), this manuscript presents a review of 10 American studies and one English study on the impact of PLCs on teaching practices and student learning. Although, few studies move beyond self-reports of positive impact, a small number of empirical studies explore the impact on teaching practice and student learning. The collective results of these studies suggest that well-developed PLCs have positive impact on both teaching practice and student achievement. Implications of this research and suggestions for next steps in the efforts to document the impact of PLCs on teaching and learning are included.
Keywords: Professional development; School culture; Student achievement; Teacher collaboration; Teaching practice